2017
DOI: 10.1038/nature21066
|View full text |Cite
|
Sign up to set email alerts
|

Gamma oscillations organize top-down signalling to hypothalamus and enable food seeking

Abstract: Both humans and animals seek primary rewards in the environment, even when such rewards do not correspond to current physiological needs. An example of this is a dissociation between food-seeking behaviour and metabolic needs, a notoriously difficult-to-treat symptom of eating disorders. Feeding relies on distinct cell groups in the hypothalamus, the activity of which also changes in anticipation of feeding onset. The hypothalamus receives strong descending inputs from the lateral septum, which is connected, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 48 publications
7
132
4
Order By: Relevance
“…4B). These high-speed variants are often used when precise control and temporal stationarity is desired, particularly in fast-spiking cells [involved in sleep, fear, and feeding (4649)]. Further engineered or naturally occurring ChRs were later identified that also exhibited fast deactivation and/or improved temporal stationarity [e.g., ChIEF, Chronos, and other variants; reviewed here (14, 41, 42, 50, 51)], and the fast-ChR toolkit grew further as ChETA and ChIEF modifications proved portable to other ChRs, including designer variants with larger photocurrents (51) and redshifted spectra (discussed below).…”
Section: Structural Models and Pore-gating Kineticsmentioning
confidence: 99%
“…4B). These high-speed variants are often used when precise control and temporal stationarity is desired, particularly in fast-spiking cells [involved in sleep, fear, and feeding (4649)]. Further engineered or naturally occurring ChRs were later identified that also exhibited fast deactivation and/or improved temporal stationarity [e.g., ChIEF, Chronos, and other variants; reviewed here (14, 41, 42, 50, 51)], and the fast-ChR toolkit grew further as ChETA and ChIEF modifications proved portable to other ChRs, including designer variants with larger photocurrents (51) and redshifted spectra (discussed below).…”
Section: Structural Models and Pore-gating Kineticsmentioning
confidence: 99%
“…Interestingly, the reciprocal VTA-LH projection is observed to be activated in response to reward omission; the disorganized feeding behavior from LH-VTA projection may occur because of the lack of this feedback information (62). Indeed, a recent study evaluating lateral septum inhibitory influence on the LH found that one subset of LH GABAergic neurons are activated during food approach and another during food consumption, indicating that a temporal sequence of GABAergic subpopulation activation occurs to produce successful food consumption (63). …”
Section: Hunger Neurocircuits Select For Increased Reward System Actimentioning
confidence: 99%
“…; Carus‐Cadavieco et al . ). Specifically, inhibitory inputs to LH neurons can drive self‐stimulation and feeding in well‐fed mice (Jennings et al .…”
Section: Identification Of the Lateral Hypothalamus As A Feeding And mentioning
confidence: 97%
“…A recent study by Carus‐Cadavieco et al . () identified a top‐down pathway connecting the medial prefrontal cortex, lateral septum (LS) and LH that uses coordinated gamma oscillations to organize feeding behaviour (Carus‐Cadavieco et al . ).…”
Section: Connectivity Of the Lateral Hypothalamusmentioning
confidence: 99%
See 1 more Smart Citation